Political Alienation and Youth Disengagement: A Political Sociological Analysis of Generation Z's Trust in The Political Party System - Syafii, Muhammad Hisyam; Azhari , Husain; Alaldaya, Rudyn (JURNAL NAWALA POLITIKA, 2025)
This study examines the phenomena of political alienation and the increasing disengagement of Generation Z from the formal political system, emphasizing their trust in political parties. This research employs a bibliometric analysis spanning 25 years (2000–2025) to chart the evolution of scholarship on teenage political disaffection, integrating theories of political alienation, political socialization, and political trust. The findings indicate that traditional frameworks insufficiently address the difficulties of political detachment in the digital age, where helplessness, meaninglessness, and isolation appear in contradictory forms. Notwithstanding Generation Z's extensive connectedness and access to political information, their trust in conventional institutions is markedly diminished. The research emphasizes the preeminence of Western scholarship in this domain, while accentuating the pressing necessity for region-specific investigations in emerging democracies like Indonesia. This research presents a refined analytical framework that incorporates structural, generational, and psychological aspects to comprehend juvenile political estrangement.